Insulin resistance syndrome manifesting as cutis verticis gyrata. - Lavery, M.J.; Parslew, R. (European Journal of Pediatric Dermatology, 2020)
Insulin resistance syndrome may be associated with acanthosis nigricans and obesity. The authors present the case of a 15 year-old girl with insulin resistance syndrome in which acanthosis nigricans and obesity were preceded by cerebriform hyperplasia of the scalp skin leading to a diagnosis of cutis verticis gyrata. In addition to the clinical manifestations of this noteworthy case, which was also characterized be the early age of onset, the authors put forward some hypotheses on its pathogenesis.